Implementation of Character Education Based on Local Wisdom in Dance Extracurriculars at Elementary Schools - Maesaroh, Maesaroh; Kustiarini, Kustiarini (UIN Raden Mas Said Surakarta, 2024)
Western culture is currently developing very rapidly along with technological developments; this has a big impact on the development of the character and morals of students in Indonesia. This research aims to (1) Describe the implementation of character education based on local wisdom in dance extracurriculars at SDN Kartasura 01 Sukoharjo; (2) Describe the values ​​of local wisdom in extracurricular dance, especially the Kebo Kinul dance at SDN Kartasura 01 Sukoharjo. This study used a descriptive qualitative method. The subjects of this research were 15 students who were active in extracurricular dance and 1 dance teacher. The data collection techniques used are observation, interviews, and documentation. The results of the research are: (1) The implementation of character education based on local wisdom in extracurricular dance at SDN Kartasura 01 Sukoharjo was carried out by preserving the regional culture of the Kebo Kinul Dance, which developed in Sukoharjo Regency; (2) The values ​​contained in the Kebo Kinul dance extracurricular are the value of working together, the value of gratitude and the value of love for the homeland. Based on the results, it can be concluded that the implementation goes through the stages of planning, implementation, monitoring, and evaluation following the curriculum to achieve national education goals